Analytical and Experimental Investigation for the Effect of Air Injection Angle on the Performance of Airlift Pump (Journal of Engineering, 2016)
The effect of air injection angle on the performance of airlift pump used for water pumping has been studied analytically and experimentally. An airlift pump of dimensions 42mm diameter and 2200 mm length with conventional and modified air injection device was considered. A modification on conventional injection device (normal air-jacket type) was carried out by changing injection angle from 90  (for conventional) to 45  and 22.5  (for modified). Continuity and one-dimensional momentum balance for the flow field with basic principle of two-phase flow and expressions of slip ratio and friction factor as function of flow rates were formulated. The analytical and experimental investigations were carried out for both conventional and unconventional air-jackets at submergence ratios 0.75, 0.6 and 0.5 and air mass flow rate from 0.5 to 97kg/hr. The comparison between the analytical and experimental results shows agreement and the main results showed that the performance and maximum efficiency of airlift pump is increased for higher mass flow rate of injected air for all tested submergence ratio using unconventional air-jacket and the higher performance was associated with injection angle 22.5 , with average enhancement were 9% and 10% for performance and maximum efficiency respectively.